Caracterización geoquímica de suelos forestales de Nothofagus pumilio (lenga) en un gradiente altitudinal en Tierra del Fuego, Argentina - Nóvoa Muñoz, Juan Carlos (2007)
Lenga forests form the dominant terrestrial ecosystem in Tierra del Fuego, spreading from sea level to 700 m a.s.l. In this altitudinal gradient, lenga trees (Nothofagus pumilio, Poepp. et Endl., Krasser) show morphological modifications due to climatic and geomorphological conditions. However, soil characteristics also play a key role in the development of these forests, especially in the supply and recycling of nutrients. Preliminary results on the geochemical characterization of lenga soils from four stands located at 220, 340, 480 and 590 m a.s.l. in the southface slope of Cerro Castor (close to Ushuaia city) is shown. The results revealed that the soils are acid (pH H2O, 3.2-5.2), with high (27-42 %) to moderate (3-4 %) C content in organic and mineral horizons and it decreases with altitude. Effective cation exchange capacity (eCEC) ranges from higher than 25 cmolc.kg-1 in the organic horizons to lesser than 11 cmolc.kg-1 in the mineral horizons. Exchangeable Ca tends to diminish with the altitude whereas Na and K showed an opposite trend. Iron and Al distribution in soil solid phase revealed that Al, Fe- humus complexes (extracted with Na-pyrophosphate) are the dominant fraction in these soils.